PENGARUH KOMPETENSI, MOTIVASI TERHADAP KEPUASAN KERJA DAN DAMPAKNYA TERHADAP KINERJA PADA BANK SYARIAH INDONESIA AREA JAMBI - Oriza Triani Wulandari; Novi Mubyarto; Bahrul Ma'ani (Universitas Islam Negeri Sumatera Utara, 2022)
The purpose of this study is to find out the influence of competence, motivation on job satisfaction and its impact on performance in Indonesian Sharia banks in jambi area. This research uses descriptive qualitative that seeks to reveal the most important concepts and realities to be presented. Hypotheses are tested through multiple regression tests. The purpose of this test is to find out if there is an influence between two variables. This study used a sample technique using the formula slovin which numbered 100 people in the Islamic bank Jambi.The results of this study prove that there is an influence of competence, motivation and job satisfaction on the performance of Indonesian Islamic banks partially and simultaneously. Competency variables have a positive and insignificant effect through statistical test proof with acalculated t value of 0.041 smaller than ttable 1.664 sig value 0.064 > 0.05, motivation positive and insignificant effect on performance is proven through statistical tests with atcalculated value of 1.005 smaller than ttable 1,664 Sig value 0.294 > 0.05, the area of work has a positive and significant effect on performance through statistical test proof with a calculation value of 0.886 smaller than ttable 1,664 sig value 0.378> 0.05 on the performance of Bank Syariah Indonesia Jambi area. Keywords: Competence, Motivation, Job Satisfaction, Performance